"Discontented scoundrels who crowd the mercantile marine today" Labour relations regimes of the Cape and Ichaboe guano trade, c. 1843-1898 (Historia, 2021)
The scraping of guano on offshore islands in the Atlantic and Pacific oceans during the mid- to late nineteenth century was an essentially primitive industry. As guano is a natural product with no further need for processing, the primary task of guano workers was the physical collection of guano chunks using basic tools such as crowbars, spades and wheelbarrows. Working on nearly barren islands with non-existent harbour facilities in remote areas far removed from its supply source, meant that guano-collection was an extremely risky enterprise and guano-labour was both back breaking and hazardous labour. Motivated by profit considerations, guanopreneurs and the Cape colonial state established and maintained an exploitative and coercive labour regime characterised by the use of deferred wages, credit and rationing as well as rigid contract enforcement. Guano diggers, however, did not accept these practices passively and as this article demonstrates, actively resisted their exploitation and marginalisation. As a result, the Cape colonial authorities were compelled to intervene, changing the system in 1898.  Ghwanoversameling met behulp van basiese tegnologie (kruiwaens, pikke, grawe en koevoete) op dikwels afgeleë en onherbergsame kuseilande aan die Atlantiese kus, het tot gevolg gehad dat die 19de eeuse bedryf tereg as primitief, en werksomstandighede as onaangenaam en lewensbedreigend beskryf is. Teneinde kostes laag te hou en maksimale voordeel uit die bedryf te verkry, het beide die Kaapse koloniale owerhede en ghwano-entrepeneurs nie gehuiwer om werkers uit te buit en 'n verdrukkende arbeidsbedeling gekenmerk deur voedselrantsoenering, kredietverlening, beperkende kontrakte en uitgestelde betalings in te stel en instand te hou nie. Verdermeer het hulle toegang tot die koloniale strafregstelsel gebruik om kontrakbreuk en drostery tot die minimum te beperk. Die ghwano arbeidsmag het egter nie hierdie situasie stilswyend aanvaar nie en het, soos wat dit uit hierdie artikel blyk, hulle aktief teen uitbuiting en marginalisering verset. Gevolglik is die Kaapse owerhede gedwing om op te tree en met ingang vanaf 1898 die stelsel waarop die ghwanobedryf voortaan bestuur sou word, wesenlik verander.
Keywords: Kaap Kolonie; Cape Colony; Verset; Slavery; Fertiliser; Ghwano; Ichaboe eilande; Guano; Ichaboe islands; Labour regime; Resistance; Arbeidbedeling; Bemesting